(untitled) (International Journal of Food and Nutritional Sciences, 2022)
This research focuses on the implementation of an environmental sustainability program through best creative housekeeping practices for this 5-star hotel in Pune. It is thought that the housekeeping department may significantly improve a hotel’s environmental sustainability. Hoteliers should integrate sustainable environmental practices into their regular business operations in order to stay on top of the detrimental effects on the environment. This study aims to investigate the most cutting-edge, environmentally responsible housekeeping procedures and their application at a different type of hotel with a higher star rating. The survey looked at five-star hotels. 104 people responded, and the data collected shows basichousekeeping practices followed but effective innovative housekeeping practices need to followed to achieved environmental sustainability programmed more effectively